Setting one voluntary standard in a heterogeneous Europe: EMAS, corruption and stringency of environmental regulations - Stefan Borsky; Esther Blanco (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
This article addresses the mediating effect of corruption on the influence of stringency of environmental regulation on firms' voluntary environmental performance. Using panel data from adoption of the EU Eco-Management and Audit Scheme (EMAS) across European Union countries from 1995 to 2011, we unveil a direct and an interacting effect of countries' corruption and regulatory stringency on the rate of adoption. First, stricter environmental regulation reduces the rate of EMAS certificates, thus supporting a crowding-out effect of mandatory regulation on voluntary action. Second, increased corruption reduces the rate of EMAS certificates. Third, the negative effect of stringency of regulation on EMAS certification rates is reinforced by corruption. In sum, these results suggest that previous studies address- ing the implications from stricter regulations on firms' voluntary action that abstract from corruption might underestimate the potential negative effect of stringency of regulation on firms' voluntary action.
Keywords: F53; Q23; Q27; F18; L15; 330; voluntary environmental action; environmental taxes; corruption; negative binomial regression